Non-invasive prenatal diagnosis based on cell-fre fetal DNA: update - Ventura Laveriano, Walter Ricardo (2014)
The discovery of cell free fetal DNA (cff-DNA) in maternal circulation has profoundly changed the clinical practice of Obstetrics and knocked down an old paradigm in prenatal diagnosis. Over the past five years screening for chromosomal abnormalities has moved from one with a high false positive rate into another more effective and at lower false positive rate. Undoubtedly, this test is the best effective screening tool in Obstetrics.